2009
DOI: 10.18296/cm.0115
|View full text |Cite
|
Sign up to set email alerts
|

The status of Te Ātiawa histories of place in Port Nicholson Block (Wellington, Hutt Valley) secondary schools: Some research findings

Abstract: this article outlines the research methodology and some key findings from my doctoral research project (Manning, 2008), which examined the status of te Ätiawa histories of place in Port Nicholson Block secondary schools' history classes. it describes the research participants' experiences of cultural continuity and discontinuity experienced in familial and secondary school settings when learning about the past. it also describes the participants' history topic preferences, and their perceptions of the benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 2 publications
4
31
0
Order By: Relevance
“…They saw little relevance between the passive learning of textbook-driven lessons to their own lived experiences. The research of Harrison and Greenfield (2011, p. 74) drew similar conclusions to those of Clark (2008) and Manning (2009); especially when they observed that: Aboriginal knowledge is told and relived in that [Indigenous] community [i.e. exosystem ] and hence learning is local, it is produced in context and place.…”
Section: The Ecological Systems Model and The Lesson Observedsupporting
confidence: 58%
See 4 more Smart Citations
“…They saw little relevance between the passive learning of textbook-driven lessons to their own lived experiences. The research of Harrison and Greenfield (2011, p. 74) drew similar conclusions to those of Clark (2008) and Manning (2009); especially when they observed that: Aboriginal knowledge is told and relived in that [Indigenous] community [i.e. exosystem ] and hence learning is local, it is produced in context and place.…”
Section: The Ecological Systems Model and The Lesson Observedsupporting
confidence: 58%
“…The lesson observed by this writer mirrored problems found by researchers in the United States and Australia. Like Manning's New Zealand research (Manning, 2009); Clark (2008) found that many Australian teachers felt uncomfortable dealing with Indigenous subject matter. They, like the New Zealand teachers interviewed by Manning; were struggling to motivate students to engage with Indigenous histories taught via repetitive textbook-driven lessons.…”
Section: The Ecological Systems Model and The Lesson Observedmentioning
confidence: 97%
See 3 more Smart Citations